The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/nu9030255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol Supplementation on  Methotrexate Chemotherapy‐Induced Bone Loss

Abstract: Intensive cancer chemotherapy is known to cause bone defects, which currently lack treatments. This study investigated the effects of polyphenol resveratrol (RES) in preventing bone defects in rats caused by methotrexate (MTX), a commonly used antimetabolite in childhood oncology. Young rats received five daily MTX injections at 0.75 mg/kg/day. RES was orally gavaged daily for seven days prior to, and during, five-day MTX administration. MTX reduced growth plate thickness, primary spongiosa height, trabecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…In MTX-treated group, a statistically significant increase in the mean value of RANKL/OPG ratio was reported, as compared to the other experimental groups. These findings are in accordance with [17] who suggested the important role of this osteoclastogenic factor in promoting osteoclasts formation and bone resorption, following MTX-chemotherapy. Moreover, [22] demonstrated that, MTX could increase osteoclasts density and reduce osteogenic differentiation; accompanied by reduction in mRNA expression of osteogenic factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In MTX-treated group, a statistically significant increase in the mean value of RANKL/OPG ratio was reported, as compared to the other experimental groups. These findings are in accordance with [17] who suggested the important role of this osteoclastogenic factor in promoting osteoclasts formation and bone resorption, following MTX-chemotherapy. Moreover, [22] demonstrated that, MTX could increase osteoclasts density and reduce osteogenic differentiation; accompanied by reduction in mRNA expression of osteogenic factors.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, [22] demonstrated that, MTX could increase osteoclasts density and reduce osteogenic differentiation; accompanied by reduction in mRNA expression of osteogenic factors. Similarly, [17] observed, upregulation of RANKL/OPG ratio and proinflammatory cytokines such as TNF-α, IL-1 and IL-6 in MTX-treated rats.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The above‐mentioned study, moreover, highlighted potential differential concentration effects of resveratrol on bone health in normal rats versus MTX‐treated rats, showing that while resveratrol at 10 mg/kg/day did not affect bone health in normal rats (which is consistent with a report that resveratrol at 20 mg/kg/day was not harmful in healthy rats), it aggravated bone damage in MTX‐treated rats (in contrast to no aggravated effects at 1 mg/kg of resveratrol) . The differential concentration effects could be related to a possible drug interaction (between resveratrol and MTX) on bone tissue.…”
Section: Potential Strategies For Preventing Methotrexate‐induced Bonsupporting
confidence: 84%
“…The efficacy of resveratrol to prevent MTX chemotherapy–induced bone defects was recently explored . In young rats treated acutely with MTX, resveratrol supplementation at 1 mg/kg was found to preserve the growth plate structure and the endochondral bone growth function, maintain expression of genes involved in osteogenesis, decrease expression of adipogenic and osteoclastogenic factors, and thus attenuate bone marrow adiposity and inhibit MTX‐induced osteoclast formation in the bone marrow of treated rats.…”
Section: Potential Strategies For Preventing Methotrexate‐induced Bonmentioning
confidence: 99%